The Role of Green Sukuk for Sustainable National Development: Peran Green Sukuk terhadap Pembangunan Nasional yang Berkelanjutan - Hiljannah, Zalfa Zahirah; Desfiansyah, Fadlan; Putra, Anggi Tryfinza; Sarjono, Oka Raditya (Universitas Siliwangi, 2023)
In this increasingly advanced era, sukuk has experienced more innovative developments with the emergence of interesting ideas in the form of green sukuk or green bonds. The issue of sustainability is being discussed more frequently due to its positive impact on the environment and future livelihoods. However, there are still individuals who are not fully aware of the importance of this concept, which can pose a serious threat to future survival. Therefore, the momentum of the sustainability movement should receive attention from the entire society, gradually understanding and implementing the concept of